Degreening Of Baramasi Lemon {Citrus Limon (L.) Burm} In Response To Ethephon Application (Applied Biological Research, 2018)
Harvesting of summer crop of Baramasi lemon (Citrus limon) coincides with  the rainy season that leads to low marketdemand and poor returns to the  growers. Therefore, an experiment was planned for post-harvest degreening  of lemon fruits to advance the marketing. Fully mature fruits of lemon cv. ‘PAU Baramasi Lemon-1’ were treated with different concentrations of  ethephon solution viz., 0, 500, 750, 1000, 1250 and 1500 ppm for 5 min. Treated  fruits were packed in CFB boxes with paper lining and kept at room  temperature. Experimental fruits were analysed for physicochemical  characteristics from 4th to 7th day after treatments at 24 h interval. Results  revealed that maximum degreening of fruits occurred with ethephon @ 1500  ppm, which was depicted by ‘b*’ value (49.37, 50.83) of colour flex meter and  these results were at par with ethephon @ 1250 ppm treatment. Similar trend  was recorded for other parameters viz., physiological loss in weight, sensory  quality, juice content, total soluble solids and acid content. It may be  concluded that lemon fruits of cv. ‘PAU Baramasi Lemon-1’ harvested in June can be degreened in 6-7 days at room temperature by dipping in 1250 or 1500  ppm of ethephon so as to advance the marketing of summer crop.
Keywords: Degreening; fruit colour; lemon; physiological loss in weight; total soluble solids